Effect of substituting cashew nut paste (Anarcadium occidentale) with baking fat on the quality of acha (Digitaria exillis) -Orange Fleshed Sweet Potato (Ipomoea batatas) Based Biscuit - Ayo, Jerome; Gbuusu, Bem; Omosebi, Mary; Kundam, Dorcas; Myange, Levy (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2024)
The aim of this research was to determine the effect of substituting cashew nut paste into baking fat on the quality of acha-orange fleshed sweet potato base biscuits. Preliminary studies was carried out on acha-OFSP at ratio 100:% acha, 95:5% acha-OFSP; 90:10% acha-OFSP, 85:15% Acha-OFSP, 80:20%, 75:5% acha-OFSP and ratio 80:20 of acha-orange fleshed sweet potato flour blends was preferred by the panellist to be used in the maim work. The experimental design were coded as follows: A-100:30:0, B-100:25:5, C-100:20:10, D-100:15:15, E-100:10:20, F-5:25, G-100:0:30 of acha-orange fleshed sweet potato: baking fat: cashew nut paste blends. The biscuits produced were analysed for proximate, minerals, vitamins, phytochemical, physical and sensory of blends biscuits. The proximate composition of the biscuit; moisture, fat, fibre, ash, protein, carbohydrate ranged from 5.96-13.36, 15.26-24.41, 1.43-2.31, 0.94-1.44 12.47-22.60, 47.20-59.99. Minerals composition of the biscuit; Ca, K, Mg and P, ranged from 35.54-49.46, 44.64-63.50, 23.13-40.73, 11.43-21.50. Vitamins composition of the biscuit; E, B2, B12 ranged from 0.32-0.48, 0.20-0.56, 0.09-0.36. Phytochemicals composition of the biscuit; flavonoids, carotenoids and phenolic ranged from 1.09-1.66, 2.08-2.57, 10.46-17.91. Physical properties; break strength, diameter, thickness, volume, weight and density ranged from 927.50-3442.50(g), 3.70-3.78(cm), 0.26-0.28(mm), 10 (cm), 5.38-6.72(g), 0.53-0.70. The average means of the aroma, texture, colour, taste and overall acceptability range from 5.90-6.75, 4.60-6.85, 5.26-7.30, 5.30-7.05, 5.65-6.80.The substitution of cashew nut paste into baking fat improved the micro, macro nutrients content and the physical of acha- OFSP flour blends based biscuits.